Comparative Study of 35% Glycolic Acid (GA) Peel versus 15% Trichloroacetic Acid (TCA) in Patients Primed with 4% Hydroquinone and Sun Block for the Treatment of Melasma - Javed, Zaaraa; Khan, Qamar Uddin; Naeem, Uzma; Zafar, Hunzala (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the effects of 35% Glycolic acid (GA) peel versus 15% Trichloroacetic Acid (TCA) in patients primed with 4% Hydroquinone and sunblock for Melasma treatment. Study Design: Quasi-experimental stud. Place and Duration of Study: Department of Dermatology, Combined Military Hospital, Jhelum Pakistan, from Jul to Nov 2020. Methodology: Forty-eight melasma patients were included and divided randomly into two groups; Group-A patients were treated with 15%Trichloroacetic Acid (TCA), while Group-B patients were treated with 35% Glycolic Acid (GA). Peeling was performed fortnightly in 4 sessions. Melasma area and severity index (MASI) scoring was calculated before and after peeling. Results: In our study, we found that pre-treatment MASI score in Group-A Trichloroacetic Acid (TCA) was 9.25±3.11 and in Group-B Glycolic Acid(GA), the pre-treatment MASI was 18.42±7.24, (p<0.001). The post-treatment MASI score in Group- A (TCA) was found to be 4.52±2.77and in Group-B (GA), it was 8.67±4.30, (p<0.001). TCA was associated with more burning, frosting, and skin cracking, while Glycolic Acid (GA) was associated with a scale of no to mild pain and mild burning. Conclusion: Both the peeling agents, 35% Glycolic Acid (GA) peel and 15%Trichloroacetic Acid (TCA), in patients primed with 4% Hydroquinone and sunblock, are effective in reducing MASI scores. However, TCA showed better results.